(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
This article discusses the archaisms, their distinctive characteristics, identifying traits, and categorization issues associated with them. Additionally, various views on classifying a language’s vocabulary according to how it is used Components are described, and the distinction between historic terms (historisms) and archaic words (archaisms) is examined.Additionally, many methods for categorizing ancient terms and their categories are described.